2019
DOI: 10.1088/1741-2552/ab4024
|View full text |Cite
|
Sign up to set email alerts
|

Computational modeling of the effects of EEG volume conduction on functional connectivity metrics. Application to Alzheimer’s disease continuum

Abstract: Objective. The aim of this study was to evaluate the effect of electroencephalographic (EEG) volume conduction in different measures of functional connectivity and to characterize the EEG coupling alterations at the different stages of dementia due to Alzheimer’s disease (AD). Approach. Magnitude squared coherence (MSCOH), imaginary part of coherence (iCOH), lagged coherence (lagCOH), amplitude envelope correlation (AEC), synchronization likelihood (SL), phase lag index (PLI), phase locking value (PLV), and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 63 publications
6
50
0
Order By: Relevance
“…The signi cant differences for iCoh were found in the lower frequency bands involving parietal-frontal connections [41]. Phase based measures have also reported increases in the theta band connectivity [42]. Similar to previous studies, signi cant differences in iCoh between EF and RF were found in the theta and beta2 band in our study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The signi cant differences for iCoh were found in the lower frequency bands involving parietal-frontal connections [41]. Phase based measures have also reported increases in the theta band connectivity [42]. Similar to previous studies, signi cant differences in iCoh between EF and RF were found in the theta and beta2 band in our study.…”
Section: Discussionsupporting
confidence: 89%
“…ROIs with remaining all other 67 ROIs. We have estimated the functional connectivity at eight frequency bands (delta[1][2][3][4], theta[4][5][6][7][8], alpha1[8][9][10], alpha2[10][11][12], beta1[12][13][14][15], beta2[15][16][17][18][19][20], beta3[20][21][22][23][24][25][26][27][28][29][30], and gamma[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45].2.3 ...…”
mentioning
confidence: 99%
“…The simulated data results were consistent with the real-data used in this paper where the best results also were obtained for positive . The better performance can be of particular importance for such real-world applications like electroencephalography (EEG) and magnetoencephalography in which the volume conduction effect can cause IC [ 18 ]. There are also other frameworks like compensated transfer entropy [ 31 ], which tries to improve the estimation of the TE in the presence of IC.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, it can occur due to fast sharing information [ 31 ]. For example, in neuro-physiological time series like EEG, the recorded electrical activity at each electrode located at the scalp, is considered to be a mixture of the source generators because the sources pass through the volume conductor [ 18 ]. The volume conduction can be considered as the zero lag coupling which may lead to detection of false directed dependency by the NUE algorithms.…”
Section: Simulation Studymentioning
confidence: 99%
See 1 more Smart Citation